Incidence of aplastic anemia and agranulocytosis in Latin America: The LATIN study - Hamerschlak, Nelson (2005)
CONTEXT AND OBJECTIVE: Aplast ic a nem ia anel agranulocytosis are rare but lile-threatening disorders, olten caused by drug s and other environmental exposures. Reported inc idence oi lhese diseases seems to vary between dillerent geograph ic regions, and lew data on their incidence are available for Latin American countries. The aim oi th is work is to delerm ine the incidence oi agranulocytosis and aplastic anemia in Brazil. DESIGN AND SETllNG: lncidence study. Seven centers took part in the pilot phase, so as to represenl ali Brazil ian regions. METHODS: Each center conducled an active search for new cases in a delined reg ion by means oi regular contacts with all hemalologisls, main clinicai laboratories and clinicians in hospitais oi the reg ion. RESULTS: 74 patients with aplastic anemia and 16 with agranulocytosis were idenlilied. Patienls with agranulocytosis had a median age oi 31 years (interquartile range, IQR: 12 .5-48.2); 32.2% were male and 81.2% were white. The median age oi aplaslic anemia patients was 21 years (IQR 15.0-35.2); 62.2% were male, 50.0% were white and 39.2% mulatto. The incidence oi agranulocytosis was eslimated to be 0.5 cases per million individuais per year, rang ing lrom O. O lo 1 . 1 cases per m ill ion per year belween regions. The incidence oi aplastic anemia was 2 .7 cases per m illion per year, ranging lrom 1.1 lo 7.1 cases per million per year between reg ions. CONCLUSIONS: Aplastic anemia and agranulocytosis are rare diseases in Brazil. However, there is considerable variabilily in their incidences between d illerent regions.